Electrochemical processes that occur in the oral cavity in patients with presence of metal inclusions (lecture) - Тимофеев, Алексей Александрович; Ушко, Наталия Алексеевна; Тимофеев, Александр Алексеевич; Кабанчук, Сергей Викторович; Ярифа, Мария Алексеевна (Actual Dentistry, 2019)
Purpose: tell students, interns and doctors about the electrochemical processes that occur in the oral cavity in the presence of non removable dental metal prostheses made of base metals. Methods. On the basis of literature data and own surveys, the issue of changes in the cavity in the presence of metal inclusions is considered in detail. Results. Based on the literature data and own surveys of patients with the presence of metal inclusions in the cavity of the mouth, details of the changes observed in the oral cavity in the presence of metal inclusions (non-removable cantilever or bridge-like dentures, pins, etc.) are described in detail. Conclusions. It is established that in the presence of non-removable metal dentures in the cavity of the mouth made of base metalalloys there are changes that lead to the development of galvanism or galvanosis. Key words: metals, non-removable dentures, saliva, oral cavity, mucous membrane, pathology, inflammation, complications, immunity, galvanism, galvanosis.